Palm Sugar Value Addition in Palm Sugar Agroindustry - Yuli Purbaningsih; Helviani Helviani; Ahmad Tarmizi Abdul Karim; Andri Estining Sejati (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2022)
The existence of agroindustry in rural areas is expected to increase the demand for agricultural products and play a role in converting agricultural products into value-added goods. The purpose of this study is to determine the value addition and efficiency of the sugar palm agro-industry in Tinggo village, Tanggetada district, Kolaka regency. The data analysis method used is Hayami's value-added analysis and R/C ratio analysis. The results showed that the added value of sugar palm was Rp 1.750/unit, which means that the income of actors in the sugar palm agribusiness increased by an additional Rp 1.750/unit. And the value of the R/C ratio is 1.73, which means the palm sugar agroindustry is feasible to develop.